Perioperative outcomes of robotic-assisted laparoscopic radical prostatectomy, laparoscopic radical prostatectomy and open radical prostatectomy: 10 years of cases at Ramathibodi Hospital - Kun Sirisopana (2020)
© 2019 AME Publishing Company. All rights reserved. Background: This study aims to compare the perioperative and pathological outcomes of open radical prostatectomy (ORP), laparoscopic radical prostatectomy (LRP), and robotic-assisted laparoscopic radical prostatectomy (RALRP) at Ramathibodi Hospital within Mahidol University in Thailand. Methods: From January 2008 to July 2017, 679 RPs were performed. Patients' data were collected retrospectively to evaluate their perioperative and pathological outcomes. This data included the age, body mass index (BMI), serum prostate specific antigen (PSA) level, clinical stage, Gleason score (GS) from biopsy, operative time, estimated blood loss (EBL), perioperative complications, blood transfusion rate, adjacent organ injury rate, length of hospital stay, pathological stage, GS of the biopsy specimen, specimen weight (g), and marginal status of the patients. Results: Of the 679 RPs performed, 128 (19.28%) were ORPs, 241 (36.30%) were LRPs, and 295 (44.43%) were RALRPs. Patients who underwent a RALRP had a significant advantage in EBL (1,600, 500, and 300 mL for ORPs, LRPs, and RALRPs, respectively), overall complications, and blood transfusion rate. As they are minimally invasive techniques, LRP and RALRP presented an advantage in terms of the length of hospital stay (an average of 9, 6, and 6 days for ORPs, LRPs, and RALRPs, respectively) and adjacent organ injury rate. ORPs also had the shortest operative time (160, 210, and 200 min for ORPs, LRPs, and RALRPs, respectively). However, the specimen weight and marginal status were similar in all of the techniques. Conclusions: Minimally invasive RP techniques, such as LRPs and RALRPs, appear to be safe, have significantly better perioperative outcomes than ORPs, and have comparable pathological outcomes to those of ORPs.